Pré-tratamentos dentinários: efeito na resistência de união utilizando sistema adesivo universal - Monteiro, Leticia Lese (2014)
The aim of this study was to evaluate the effect of dentin pretreatment with chlorhexidine and sodium hypochlorite in the bond strength of adhesive systems. Seventy-two sound human third molars were divided in 12 groups according to the adhesive system (Single Bond 2 - SB2, Clearfil SE Bond - SE, Single Bond Universal - SBU ) pretreatment (control, 2% chlorhexidine and hypochlorite sodium 10% ) and strategies ( self-etching or total etching ). The adhesive protocols followed the recommendation of the respective manufacturers and resin restorations were made of 5mm. After restoration, the teeth were stored in distilled water for 24 hours and sectioned to obtain specimens with interface area of 1.0 mm². Then, the specimens were subjected to microtensile testing in a universal testing machine until its failure. The results of the test microtensile bond strength were recorded in Mpa. Mean and standard deviation were calculated for each of the experimental groups. The mean bond strengths were subjected to analysis of variance (ANOVA) and differences between groups were assessed by Tukey test. For all analyzes the significance level was 5%. Analysis of variance showed that treatment surface factor exerted significant influence on the values of bond strength. The use of sodium hypochlorite to 10 % reduced the values of bond strength when compared to other treatments for all adhesive systems and should not be considered as a pretreatment of dentin.